Molecular compositions and optical properties of water-soluble brown carbon during the autumn and winter in Guangzhou, China. (1st March 2023) - He, Tan; Wu, Yang; Wang, Dian; Cai, Jing; Song, Jianzhong; Yu, Zhiqiang; Zeng, Xiangying; Peng, Ping'an
Abstract: Brown carbon (BrC) has attracted increasing attention due to its significant effects on the atmospheric environment and climate. In this study, we investigated the seasonal variations of the optical and molecular properties of water-soluble BrC in Guangzhou and the key factors affecting its light absorption and fluorescence properties. The mass absorption efficiency at 365 nm (MAE365 ) indicated that water-soluble BrC had a stronger light absorption capacity in winter than in autumn. An excitation emission matrix-parallel factor analysis (EEM-PARAFAC) identified four fluorescent components (C1–C4) in the water-soluble organic compound (WSOC) fraction, of which the humic-like components (C1, C2, and C4) were the dominant fluorophores. More C1 and C4 components were detected in autumn WSOC, whereas more C3 component in winter WSOC, which was mainly due to the differences in the sources and oxidation processes of WSOC in different seasons. The molecular composition of WSOC also indicated significant seasonal variations as revealed by an electrospray ionization ultrahigh-resolution mass spectrometry (ESI-UHRMS) analysis. The autumn WSOC had a higher degree of oxidation, whereas the winter WSOC had a higher aromaticity. Furthermore, a principal component analysis (PCA) and the Pearson correlation coefficients indicated that the light absorption of water-soluble BrC over Guangzhou was mainly affected by their aromaticity and N-containing species, with aromatic CHO and CHON compounds being the most important chromophores. The fluorescent components C1 and C4 were characterized by a relatively high oxidation level, which may be more relevant to aged organic aerosols with a high aromaticity and oxidation. The fluorescent component C3 may be more relevant to the primary emission of organic aerosols or fresh organic aerosols with low oxidation, and some non-nitrogen-containing species also had associations with previously assigned protein-like components (C3). Highlights: Season differences in molecular and optical properties of BrC was investigated. Differences in source and oxidation lead the variation of optical properties of BrC. The molecular composition of BrC is related to its source and oxidation process. Light absorption of BrC is mainly affected by its aromaticity and N species. The molecular composition of EEM-PARAFAC component were revealed.